STIMULASI KREATIVITAS ANAK MELALUI MEMBUAT KARYA BAHAN LOOSE PART - Eneng Garnika; Baiq Rohiyatun (Jurnal Dedikasi Madani, 2024)
The use of Loose Parts media in learning plays a role in developing creativity in early childhood by carrying out all stages of using Loose Parts media using play strategies, strategies for cleaning up and storing things as well as various strategies for increasing creativity (product creation, imagination, experimental exploration, projects, music and language). In this regard, schools and parents need to establish good cooperation so that they can optimize the use of Loose Parts media to develop creativity in early childhood.